ANALYSIS OF FISCAL POLICY IN MANAGING THE STATE BUDGET IN INDONESIA PRE AND POST COVID-19 - Wartoyo, Wartoyo; Pratiwi, Lisa; Awaliya Rahma, Tiara (Institut Agama Islam Negeri (IAIN) Bone, 2024)
The purpose of this study is to analyze fiscal policy in the management of the State Budget in Indonesia. The method used is descriptive analysis, which means explaining and describing both oral and written forms derived from literature studies. The results of the study show that the fiscal policy used in Indonesia is an expansionary fiscal policy marked by a state budget that is classified as a deficit. Then, to increase state revenue, the government began to export downstream commodities that had high added value. In order to minimize state spending, the government implements zero-based budgeting. This can be said to be able to increase the value of the state budget in its management.